KESADARAN SPIRITUAL SEBAGAI RUH KEPEMIMPINAN KEPALA MADRASAH DALAM UPAYA PROFESIONALISASI GURU DI MA Al-KARIMIYAH - Ahmad Damanhuri (Universitas Islam Depok, 2022)
Spiritualism is a spirit that is often overlooked. In fact, spiritual awareness is very important, especially in stemming the flow of modern education which is secular in nature. Article 1 of the National Education System Law has explained that one of the goals of education is to have religious spiritual strength. There are at least ten criteria used to measure a person's spiritual intelligence, namely 1) Self-Awareness, 2) Spontaneity, Internally motivated, 3) Seeing life from a vision based on fundamental values, 4) Holistic, seeing systems and universality, 5) Compassion, 6) Firm in adversity, 7) Rearrange in the big picture, 8) Questioning fundamentally, 9) Independent, steadfast against the majority and 10) Appreciating diversity. The spiritual awareness strategy applied by the Head of Madrasah Al-Karimiyah for performance in carrying out professional duties and responsibilities of teachers and having good performance with the aim of building commitment of educators and education staff in their work environment, so that they can actually carry out their duties, functions and responsibilities.